2016
DOI: 10.1186/s40064-016-2343-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast findings incidentally detected on body MRI

Abstract: ObjectivesTo evaluate breast findings incidentally detected on body MRI.MethodsA retrospective review of the institutional database identified 1752 body MRI performed between January 2015 and September 2015. MRI of women with breast tissue visible in the field-of-view were reviewed for breast findings. Breast findings were classified with the breast imaging reporting and data system (BI-RADS) lexicon. The standard statistic, costs of additional work-up, and the clinical relevance were used to describe breast f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Additional breast imaging examinations and procedures were recommended for at least 3.6%, and about 1% of the patients were diagnosed with breast cancer. Use of gadolinium contrast agent in abdominal MRI increases the detection rate of breast findings [27]. The lesion morphology (shape and margins), T2W signal intensity, and enhancement pattern are useful features in evaluating breast lesion and formulating a differential diagnosis.…”
Section: Chest Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional breast imaging examinations and procedures were recommended for at least 3.6%, and about 1% of the patients were diagnosed with breast cancer. Use of gadolinium contrast agent in abdominal MRI increases the detection rate of breast findings [27]. The lesion morphology (shape and margins), T2W signal intensity, and enhancement pattern are useful features in evaluating breast lesion and formulating a differential diagnosis.…”
Section: Chest Wallmentioning
confidence: 99%
“…In general, wellcircumscribed breast lesions that show high signal intensity on T2W images are benign, taking into consideration some notable exceptions such as mucinous carcinoma, medullary carcinoma, and necrotic tumors [28]. Correlation with previous imaging may help guide management of breast findings and avoid further work up [27]. • Lung nodules especially in the delayed "interstitial" phase.…”
Section: Chest Wallmentioning
confidence: 99%
“…The rate of breast incidental findings on computerized tomography has been well documented, with subsequent cancer diagnosis averaging 42% 4 . However, data on breast incidental findings on abdominal and chest MRI (MRI‐AC) are limited with significant heterogeneity in prior results 5‐7 …”
Section: Demographic N (%)mentioning
confidence: 99%
“…4 However, data on breast incidental findings on abdominal and chest MRI (MRI-AC) are limited with significant heterogeneity in prior results. [5][6][7] Our goal was to evaluate the frequency of breast incidental findings on MRI-AC, document radiologist recommendations for follow-up diagnostic breast imaging, assess the rate of compliance with follow-up, and identify factors associated with improved follow-up.…”
mentioning
confidence: 99%
“…While screening mammography rates are falling, an increasing number of low dose chest CTs, abdomino-pelvic MRIs, and 18-FDG-PET-CTs are being performed each year for diseases of the chest not related to the breast tissue itself [ 31 , 50 53 ]. Multiple studies have shown this widespread use of imaging modalities to have led to an ever-increasing rate of incidental breast lesion discovery [ 31 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%